Microbial pathogenesis and the intestinal epithelial cell - Hecht, Gail A (ASM Press, 2003)
S Harrop - Australian Journal of Medical Science, 2004 - search.informit.com.au Consisting of twenty-eight chapters which include numerous introductory sessions, this multi author work showcases the field from functional morphology of the intestinal mucosa, intestinal immunology, animal models of the human gut, invasive processes to viral pathogens. Many of the chapters are not too dissimilar to the indi- vidual authors\' previously published works, and it ap- pears that the contributors were asked to summarise their most up to date findings with a contemporary re- view of the area of speciality. Therefore, if one reads all that is published …
Keywords: Microbiological Phenomena; mikrobiologické jevy; nemoci střev; gastroenterologie; střevní sliznice; mikrobiologie, lékařská mikrobiologie; Epithelium; epitel; Intestinal Diseases; Intestinal Mucosa